Socialization to Build a Creative Culture for Start Up Business Through Digital Literacy - Nawangsih Nawangsih (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
Community service activities are carried out in Gucialit Village, Gucialit District, Lumajang Regency. The socialization activity was carried out to provide knowledge as well as understanding to partners related to the socialization of building a creative culture for start-up businesses through digital literacy, considering that digital literacy still needs to be improved, especially among the younger generation who are starting start-up businesses/start-up businesses.The problems faced by partners include: limited Human Resources who have knowledge related to marketing management, especially related to creative culture and digital literacy and the utilization of coconut shell waste into products of high economic value for the environment and creative business opportunities Solutions or alternatives offered to partners to help overcome problems include: increasing abilities, especially in knowledge and information related to marketing management, especially with regard to creative culture and digital literacy and providing new knowledge related to the use of waste to be of high economic value, and the role of digital literacy. in supporting the success of marketing activities carried out especially for start-up businesses.Community service activities in the form of socialization are expected to produce targets according to the expectations of partners, namely: increasing partner knowledge and skills related to creativity and digital literacy and providing understanding related to the role of digital literacy in supporting the success of marketing activities carried out as well as strategies for developing a creative culture for startups up business.